Comparison on selected fitness indicator and golf performances among elite and non-elite university golfers / Muhamad Safiq Saiful Annur ...[et al.] - Saiful Annur, Muhamad Safiq; Yasin, Azman; Syarif, Ahmad Farhan; Md Radzi, Noor Azila Azreen (UiTM Press, 2017)
The purpose of the study was to investigate the differences of physical fitness between elite and non-elite golfers in the National Golf Academy, UUM. The two groups were compared based on their physical fitness (leg power, muscular endurance, muscular strength, cardiovascular endurance, balance and abdominal muscle performances) and golf performances (handicap, 5-iron ball speed, 5-iron clubhead speed, 5-iron carry distance, average score, greens in regulations, and putts per round). Significant differences were found on handicap and predicted Vo2max variables (p < 0.05). Significant differences were also found on non-dominant leg vertical jump (20.6 ± 4.5 vs. 14.7 ± 5, p < 0.05) and push up performances (27.9 ± 10.1 vs. 16.4 ± 11.2, p < 0.05) between the elite and non-elite groups. Elite golfers have better performances in static balance (both dominant and non-dominant leg) and abdominal muscle performance where the significant level was found to be less than 0.05. While for golf performances, the difference between those two groups were found on the 5-iron clubhead speed, 5-iron ball speed, 5-iron carrying distance and average score (p < 0.05). These results can be used for developing training programmemes, as well as for the development of talent identification programmemes.